2008
DOI: 10.1107/s1744309108000328
|View full text |Cite
|
Sign up to set email alerts
|

Purification, crystallization and preliminary X-ray analysis of inositol dehydrogenase (IDH) fromBacillus subtilis

Abstract: Inositol dehydrogenase (IDH) is an enzyme that catalyses the NAD + -dependent oxidation of myo-inositol to scyllo-inosose. The enzyme has been purified to homogeneity by means of Ni 2+ -affinity chromatography and was crystallized in both native and selenomethionine (SeMet) labelled forms using the microbatch method. SAD X-ray diffraction data were collected to 2.0 Å resolution from a SeMet-labelled crystal at the Advanced Photon Source (APS) and a MAD data set was collected to 1.75 Å resolution at the Canadia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Expression and purification of protein for crystallization was described previously. 20 Purified protein stock was thawed and diluted 1:1 with 25 mM Tris−HCl, pH 8.0, to a concentration of 3.25 mg mL −1 and incubated with 10 mM of NADPH, on ice, for 30 min. Crystal screening was done using the microbatch technique against crystallization screens from Qiagen.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…Expression and purification of protein for crystallization was described previously. 20 Purified protein stock was thawed and diluted 1:1 with 25 mM Tris−HCl, pH 8.0, to a concentration of 3.25 mg mL −1 and incubated with 10 mM of NADPH, on ice, for 30 min. Crystal screening was done using the microbatch technique against crystallization screens from Qiagen.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…In bacteria, mI can be used as a sole carbon source. The well-characterized catabolic pathway in Bacillus subtilis , encoded by the iol operon, produces an equimolar mixture of dihydroxyacetone phosphate, acetyl-CoA, and CO 2 in six steps from mI, beginning with oxidation of the hydroxyl on C-2. ,, The enzyme that catalyzes this first step, myo -inositol dehydrogenase, is known to have a broad substrate scope but is selective for oxidation of an axial hydroxyl group. …”
mentioning
confidence: 99%
“…We have studied the enzymes in inositol catabolism of two Gram-positive bacteria, B. subtilis , and Lactobacillus casei . These studies indicated that mI dehydrogenase (mIDH) catalyzes the first step in mI catabolism by selectively oxidizing the hydroxyl group at position 2 forming scyllo -inosose (Figure ).…”
mentioning
confidence: 99%
See 1 more Smart Citation